Representasi Politik Uang Dalam Film Lansia Lan Sopo: - Pamungkas, Daniel Gelegar; Zamzamy, Ahmad (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Lansia Lan Sopo' is a film that addresses the theme of anti-corruption with the issue of political money in the implementation of village head elections. 'Lansia Lan Sopo' is directed by Alfian Alfarisi and has a duration of 15 minutes and 09 seconds. This research aims to understand how the representation of political money in the film 'Lansia Lan Sopo' is depicted in the context of two rival campaign teams during the village head election. The research uses a qualitative descriptive approach and employs John Fiske's semiotic analysis method to dissect the codes and deeper meanings in the film. The results of the research reveal various depictions of political money in the film 'Lansia Lan Sopo.' Additionally, there is also a depiction of how political money is a product of capitalist ideology. This is demonstrated through John Fiske's semiotics with three levels: the level of reality depicting the actions of political money, the level of representation showing supporting elements in each scene, and the level of ideology to understand the concepts and meanings in the film 'Lansia Lan Sopo.' Keywords: Political Money, John Fiske Semiotics, Lansia Lan Sopo